NLRP3 inflammasome and NLRP3-related autoinflammatory diseases: From cryopyrin function to targeted therapies - Moltrasio, Chiara; Romagnuolo, Maurizio; Marzano, Angelo Valerio (Frontiers in Immunology, 2022)
The NLRP3 inflammasome is one of the NOD-like receptor family members with the most functional characterization and acts as a key player in innate immune system, participating in several physiological processes including, among others, the modulation of the immune system response and the coordination of host defences. Activation of the inflammasome is a crucial signaling mechanism that promotes both an acute and a chronic inflammatory response, which can accelerate the production of pro-inflammatory cytokines, mainly Interleukin (IL)-1β and IL-18, leading to an exacerbated inflammatory network. Cryopyrin associated periodic syndrome (CAPS) is a rare inherited autoinflammatory disorder, clinically characterized by cutaneous and systemic, musculoskeletal, and central nervous system inflammation. Gain-of-function mutations in NLRP3 gene are causative of signs and inflammatory symptoms in CAPS patients, in which an abnormal activation of the NLRP3 inflammasome, resulting in an inappropriate release of IL-1β and gasdermin-D-dependent pyroptosis, has been demonstrated both in in vitro and in ex vivo studies. During recent years, two new hereditary NLRP3-related disorders have been described, deafness autosomal dominant 34 (DFN34) and keratitis fugax hereditaria (KFH), with an exclusive cochlear- and anterior eye- restricted autoinflammation, respectively, and caused by mutations in NLRP3 gene, thus expanding the clinical and genetic spectrum of NLRP3-associated autoinflammatory diseases. Several crucial mechanisms involved in the control of activation and regulation of the NLRP3 inflammasome have been identified and researchers took advantage of this to develop novel target therapies with a significant improvement of clinical signs and symptoms of NLRP3-associated diseases. This review provides a broad overview of NLRP3 inflammasome biology with particular emphasis on CAPS, whose clinical, genetic, and therapeutic aspects will be explored in depth. The latest evidence on two “new” diseases, DFN34 and KFH, caused by mutations in NLRP3 is also described.